(untitled) (Journal of the College of Basic Education, 2020)
The removal of heavy crude oil from slag from oilfields and petroleum industries was studied using the technique of extracting with a mixture of hexane-acetone solvents to investigate the ability of this mixture to clean the brownish (sludge) from heavy crude oil under different extraction conditions. The study showed that the mixture of hexane and acetone (25%) and the ratio of solid to liquid (1/6 g / ml) and temperature (40 ° C) are the most effective conditions for removing petroleum hydrocarbons from the brownish (slag). Kinetics experiments showed that the balance reached in 6 minutes and the highest extraction was 91%, and most of the oil pollutants were removed within the first minute and the percentage of removal was 50%.